Modeling study power distribution system network using digsilent power factory 13.2 simulation software - Lukman Hakimi, Ab Wahab (2009)
The reason of power flow study is to determine the steady-state operating condition of the electrical power network. The steady-state can be determined by finding out the flow of active power and reactive power throughout the network and the voltages magnitudes and phase angle all nodes of the network. Load flow studies are used to ensure that electrical power transfer from generators to consumers through the grid system is stable, reliable and economic. Using a software allow engineers to solve power system analysis more easily. This project is to produce analyze the power system network plant. It worked by using Digsilent Power Factory. The result can be divide by two which are power flow analysis and short circuit analysis. The power flow will present each voltage at each component .Like low much voltage at the bus bar, including the loading at transformer, cabal, load and motor. Short circuit analysis will initialize the initial short circuit and the peak short circuit. This result from the analysis will be used for another issue such as the safe operation and future growth of the plant.